2015
DOI: 10.1002/hep.28265
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and mechanistic potential of progesterone sulfates in intrahepatic cholestasis of pregnancy and pruritus gravidarum

Abstract: A challenge in obstetrics is to distinguish pathological symptoms from those associated with normal changes of pregnancy, typified by the need to differentiate whether gestational pruritus of the skin is an early symptom of intrahepatic cholestasis of pregnancy (ICP) or due to benign pruritus gravidarum. ICP is characterized by raised serum bile acids and complicated by spontaneous preterm labor and stillbirth. A biomarker for ICP would be invaluable for early diagnosis and treatment and to enable its differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 24 publications
3
92
0
9
Order By: Relevance
“…Liver enzymes (e.g., ALT) have a limited use as markers due to huge intrapatient variations [59,71]. Instead, an increased serum autotaxin (lysophospholipase D) activity or progesterone sulfates are novel diagnostic markers, distinguishing ICP from other pruritic disorders of pregnancy and pregnancy-related liver diseases [72,73].…”
Section: Prediction and Putative Biomarkersmentioning
confidence: 99%
“…Liver enzymes (e.g., ALT) have a limited use as markers due to huge intrapatient variations [59,71]. Instead, an increased serum autotaxin (lysophospholipase D) activity or progesterone sulfates are novel diagnostic markers, distinguishing ICP from other pruritic disorders of pregnancy and pregnancy-related liver diseases [72,73].…”
Section: Prediction and Putative Biomarkersmentioning
confidence: 99%
“…(4) Among other important steps in this research line, Glantz et al, in Sweden, reported similar changes in the pattern of progesterone metabolites in urine of ICP patients, with a reversal after ursodeoxycholic acid administration, correlating with an improvement in maternal pruritus (5) ; and Abu-Hayyeh et al also reported increased levels of progesterone sulfates in ICP patients studied in the United Kingdom. (6) Therefore, this metabolic pattern has been detected in ICP patients from different geographic locations and ethnic origins.The present study (1) identified three sulfated progesterone metabolites, 5a-pregnan-3a,-20a-diol-3,20-disulfate, 5b-pregnan-3a-20a-diol-3-sulfate, and 5b-pregnan-3a-20a-diol-3,20-disulfate, that were present in ICP patients in serum samples obtained even at 9-15 Abbreviations: ICP, intrahepatic cholestasis of pregnancy; PG, pruritus gravidarum. …”
mentioning
confidence: 60%
“…The present study (1) identified three sulfated progesterone metabolites, 5a-pregnan-3a,-20a-diol-3,20-disulfate, 5b-pregnan-3a-20a-diol-3-sulfate, and 5b-pregnan-3a-20a-diol-3,20-disulfate, that were present in ICP patients in serum samples obtained even at [9][10][11][12][13][14][15] Abbreviations: ICP, intrahepatic cholestasis of pregnancy; PG, pruritus gravidarum.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The group of Williamson has contributed greatly to this field by performing some of the most important work on the management and development of predictive biomarkers enabling targeted obstetric care to women at risk of developing obstetric cholestasis from early pregnancy on. Putative predictive biomarkers, such as autotaxin and the sulphated progesterone metabolites, 6 have been suggested and seem promising for future larger-scale studies. The authors discuss future directions in the field, including prevention of disease onset and determining which cholestasis pregnancies are associated with adverse fetal outcomes.…”
Section: Obstetric Cholestasis: a New Era Of Exciting Developmentsmentioning
confidence: 99%